Two new species of Phaeohelotium (Leotiomycetes: Helotiaceae) from Chile and their putative ectomycorrhizal status - Grupe Ii, A C; Smith, M E; Weier, A; Healy, R; Caiafa, M V; Pfister, D H; Haelewaters, D; Quandt, C A (Fungal systematics and evolution, 2022)
Species of the genus Phaeohelotium (Leotiomycetes: Helotiaceae) are cup fungi that grow on decaying wood, leaves, litter, and directly on soil. Northern Hemisphere species are primarily found on litter and wood, whereas in the Southern Hemisphere the genus includes a mix of saprotrophs as well as taxa that grow on soil in association with ectomycorrhizal trees. The diversity of this genus has not been fully explored in southern South America. Here we describe two species from Chile, Phaeohelotium maiusaurantium sp. nov. and Ph. pallidum sp. nov., found on soil in Patagonian Nothofagaceae-dominated forests. We present macro- and micromorphological descriptions, illustrations, and molecular phylogenetic analyses. The two new species are placed in Phaeohelotium with high support in our 15-locus phylogeny as well as phylogenetic reconstructions based on the internal transcribed spacer (ITS) region of the nuclear ribosomal RNA gene. Our ITS phylogeny places both Ph. maiusaurantium and Ph. pallidum in a well-supported subclade that includes ectomycorrhizal root tip samples from Australasia. Similar species can be separated from these new taxa based on morphological characteristics, biogeography, substrate, and sequence data. In addition, two unnamed species from Chilean Nothofagaceae forests (Phaeohelotium sp. 1 and Phaeohelotium sp. 2) are documented from scant collections and sequence data and await description until more material becomes available. Citation: Grupe II AC, Smith ME, Weier A, Healy R, Caiafa MV, Pfister DH, Haelewaters D, Quandt CA (2022). Two new species of Phaeohelotium (Leotiomycetes: Helotiaceae) from Chile and their putative ectomycorrhizal status. Fungal Systematics and Evolution 10: 231-249. doi: 10.3114/fuse.2022.10.10.
Keywords: multilocus phylogeny; Ascomycota; Patagonia; taxonomy; four new taxa; Nothofagaceae